AI Based Traffic and Automobile Monitoring System (International Journal of Innovative Research in Computer Science & Technology, 2024)
We live in a world where technology is  constantly changing and upgrading, so this change gave  birth to artificial intelligence (AI). When intelligence is  shown by humans it’s called human intelligence, but when  machines show such intelligence it’s called artificial  intelligence. And by this constant change in technology we  have opened doors to some new threats and humans are  incapable to measure and predict such dangers. But on the  other hand, AI in today’s era has reached such potential  that it can be used to monitor and predict many dangers.  This paper presents a technique about how we can use  artificial intelligence to monitor traffic in highways, roads  streets and in many places where we cannot put traffic  signals, and how we can monitor activity of each and every  individual vehicle to make world safer for humans and  other life forms so we can live in harmony and unison.
Keywords: Cameras; GPS; 5G; machine learning; OS; object tracking